2020
DOI: 10.1002/ijc.33323
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for aspirin in the prevention and treatment of cholangiocarcinoma

Abstract: Cholangiocarcinoma is the second most common primary hepatic cancer, with a rising incidence worldwide. Owing to late diagnosis and limited treatment options, the prognosis for cholangiocarcinoma remains dismal, compelling a search for new treatments. As aspirin exhibits a well‐supported chemopreventive effect on common cancers, researchers have proposed using aspirin as a potential preventive and adjuvant agent for cholangiocarcinoma. In the present review of the literature, we provide a background on cholang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…It is advantageous to find a new anticancer use among existing drugs that may already have an established safety profile ( 19 ). NSAIDS, such as aspirin, have been found lower risk of cholangiocarcinoma and colorectal cancer ( 20 , 21 ). Not only that, but there is a strong interest in reusing metformin to prevent cancer and cancer recurrence ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is advantageous to find a new anticancer use among existing drugs that may already have an established safety profile ( 19 ). NSAIDS, such as aspirin, have been found lower risk of cholangiocarcinoma and colorectal cancer ( 20 , 21 ). Not only that, but there is a strong interest in reusing metformin to prevent cancer and cancer recurrence ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…118 It acts via inhibition of the cyclooxygenase-2 pathway resulting in reduction of carcinogenic prostaglandin E2, 118 which is of relevance to PSC-related CCA where overexpression of cyclooxygenase-2 in biliary epithelium has been described. 3,118 It also reduces platelet aggregation with a negative impact on tumor angiogenesis and metastases, and cellular inhibition of signaling pathways that promote tumor growth. 118 Evidence for aspirin use in reduction of CCA risk is growing, [118][119][120][121] however studies investigating this specifically in PSC is lacking.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…3,118 It also reduces platelet aggregation with a negative impact on tumor angiogenesis and metastases, and cellular inhibition of signaling pathways that promote tumor growth. 118 Evidence for aspirin use in reduction of CCA risk is growing, [118][119][120][121] however studies investigating this specifically in PSC is lacking. 122 A retrospective cohort study published in abstract form demonstrated a trend toward significant reduction in risk of PSC-related CCA with aspirin use only.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Aspirin has emerged as a promising intervention in cancer treatment in the past decade (Tran et al, 2021;Lichtenberger et al, 2019), and has a protective effect against several types of cancer (Garcia-Albeniz et al, 2011;Usman et al, 2015). It induces cell death in various cancer cell lines, such as myeloid leukaemia and HeLa cells, chronic lymphocytic leukaemia cells, colon cancer cells (Bellosillo et al, 1998), gastric cancer (Gu et al, 2005), colorectal cancer (Stark et al, 2007) and cholangiocarcinoma (Shen & Shen, 2021).…”
Section: Chemical Contextmentioning
confidence: 99%